Current and Emerging Therapies for Pancreatic Neuroendocrine Tumours in Patients with or without Multiple Endocrine Neoplasia Type 1 - Frost, Morten (Nat Rev Endocrinol, 2018)
Pancreatic neuroendocrine tumours (PNETs) may occur as a non-familial isolated endocrinopathy or as part of a complex hereditary syndrome, such as multiple endocrine neoplasia type 1 (MEN1), which is an autosomal dominant disorder characterised by the combined occurrence of PNETs with tumours of the parathyroids and anterior pituitary. Treatments for primary PNETs, include surgery, and for nonresectable PNETs and metastases, treatments include biotherapy (e.g. somatostatin analogues, inhibitors of receptors, and monoclonal antibodies), chemotherapy, and radionuclide therapy. However, treatment of PNETs in patients with MEN1 is challenging due to concomitant development of tumours, which may have metastasised, and there is a scarcity of clinical trials reporting the effects of these anti-tumour therapies in PNETs of MEN1 patients. For example, clinical trials have shown that inhibitors of receptor tyrosine kinases (RTKs) and the mechanistic target of rapamycin receptor (mTOR) pathway, and antibodies to vascular endothelial growth factor A (VEGFA) are effective treatments for PNETs in non-MEN1 patients, but data from MEN1 patients is lacking. Recent preclinical studies have identified potentially new therapeutic targets for treating MEN1-associated NETs, and these include epigenetic modification, the β-catenin/Wnt-pathway, hedgehog signalling, and somatostatin receptors, as well as MEN1 gene replacement therapy. This review discusses these advances.